KONTRIBUSI MINAT TERHADAP MOTIVASI BELAJAR SISWA SMPS KRISTEN BNKP TELUKDALAM TAHUN PELAJARAN 2019/2020 - Sesilianus Fau (Institut Pendidikan Tapanuli Selatan, 2021)
This research was conducted based vary data of students’ learning motivation. Interest is predicted to have dominant contribution towards students’ learning motivation. This research was aimed at 1) describing students’ interest of SMPS Kristen BNKP Telukdalam, 2) describing students’ learning motivation of SMPS Kristen BNKP Telukdalam, and 3) testing the contribution of interest towards students’ learning motivation of SMPS Kristen BNKP Telukdalam. This research was conducted by using quantitative approach and descriptive correlational method. The population of this research was the eighth grade of SMPS Kristen BNKP Telukdalam in Academic Year 2019/2020. The sample of this research was determined by using Slovin formula and simple random sampling technique. The number of sample in this research was 59 students. The data of this were analyzed through descriptive statistic and simple linear regression assisted by Statistical Product and Service Solutions (SPSS) application. The research results showed that 1) the description of students’ interest of SMPS Kristen BNKP Telukdalam in general was in the level of high category, 2) the description of students’ learning motivation of SMPS Kristen BNKP Telukdalam was in the level of very high category, and 3) the interest had significant contribution towards students’ learning motivation of the eighth grade of SMPS Kristen BNKP Telukdalam, which was 34% (R= 0.583, R2= 0.340, dan sig. 0.000). It means that the higher students’ interest is, the higher students’ learning motivation will be.